1997
DOI: 10.1111/j.1600-0773.1997.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Novel Cholecystokinin‐B/Gastrin Receptor Antagonists: A Study of their Effects on Rat Stomach Enterochromaffin‐Like Cell Activity

Abstract: Gastrin stimulates rat stomach enterochromaffin-like (ECL) cells via activation of cholecystokinin-Blgastrin receptors. The stimulation is manifested in the activation of the histamine-forming enzyme histidine decarboxylase and in the secretion of histamine and pancreastatin, a chromogranin A-derived peptide. We have examined the short-term effects of three novel cholecystokinin-B/gastrin receptor antagonists (YF476, JB93182 and AG041R) on the ECL cells in intact fasted rats. The drugs and/or gastrin were infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…This effect involves activation of CCK1R, as evidenced by studies with antagonists in rats and humans (131,154,437,459,591). Reduction of gastric emptying by a specific CCK1R agonist is also consistent with a CCK1R-mediated mechanism (80).…”
Section: Stomachmentioning
confidence: 69%
See 1 more Smart Citation
“…This effect involves activation of CCK1R, as evidenced by studies with antagonists in rats and humans (131,154,437,459,591). Reduction of gastric emptying by a specific CCK1R agonist is also consistent with a CCK1R-mediated mechanism (80).…”
Section: Stomachmentioning
confidence: 69%
“…In several rat studies, treatment with CCK2R antagonists caused changes in ECL cell activity, indicating the presence of the receptor on these cells (131,195). Binding and functional studies demonstrated that both CCK1R and CCK2R are present on guinea pig chief cells (91, 389).…”
Section: Stomachmentioning
confidence: 99%
“…As a control, we also assessed the drug effects on plasma gastrin levels and on cell proliferation in the normal oxyntic mucosa (10,11). Omeprazole and YF-476 caused approximately a sevenfold increase in plasma gastrin levels and a slight, but significant, increase in cell proliferation of the oxyntic mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…AG-041R, a potent and specific gastrin receptor antagonist (Ding et al, 1997;Chiba et al, 1998;Fukui et al, 1998;Hakanson et al, 1999), was a gift from Chugai Pharmaceutical Co., Ltd. (Tokyo, Japan). NS-398, a specific inhibitor of COX-2 (Futaki et al, 1993a,b;Masferrer et al, 1994;Tsuji et al, 1996), was purchased from Cayman Chemicals (Ann Arbor, MI).…”
Section: Methodsmentioning
confidence: 99%
“…The functionally defined receptors for gastrin include cholecystokinin A receptor, which is discriminating for sulfated CCK 8 ; gastrin/cholecystokinin B (CCKB) receptor, which binds gastrin 17 sulfated and nonsulfated CCK 8 with nearly equal affinities; cholecystokinin C, which is a low-affinity gastrin binding protein; and novel, high-affinity receptors selective for amidated gastrin, processing intermediates of gastrin, or both (Yassin, 1999). We also examined the influences of a gastrin/CCKb receptor antagonist (Ding et al, 1997;Chiba et al, 1998;Fukui et al, 1998;Hakanson et al, 1999) on gastric mucosal expression of cyclooxygenase and gastric mucosal protection.…”
mentioning
confidence: 99%